Construções euclidianas e o desfecho de problemas famosos da geometria - Precioso, Juliana Conceição [UNESP]; Pedroso, Hermes Antonio [UNESP] (My University, 2011)
Construction techniques with ruler and the compasses, fundamental on Euclidean geometry, have been related to modern algebraic theories such as solving equations and extension of bodies from the works by Paolo Ruffini (1765-1822), Niels Henrik Abel (1802-1829) and Evariste Galois (1811-1832). This relation could provide an answer to some famous problems, from ancient Greece, such as doubling the cube, the trisection Angle, the Quadrature of the Circle and the construction of regular polygons, which remained unsolved for over two thousand years. Also important for our purposes are the notions of algebraic numbers, transcendental and the criteria for constructability, of those numbers. The objective of this study is to reconstruct relevant steps of geometric constructions with ruler (unmarked) and the compasses, from the elementary to the outcome buildings, in the nineteenth century, considering those mentioned problems.

As técnicas de construção com régua e compasso, fundamentais na geometria euclidiana, foram relacionadas com teorias algébricas modernas, tais como, da resolução de equações e extensão de corpos, a partir dos trabalhos de Paolo Ruf- fini (1765-1822), Niels Henrik Abel (1802-1829) e Évariste Galois (1811-1832). Desse relacionamento, foi possível dar uma resposta a alguns problemas famosos, desde a Grécia Antiga,a exemplo da Duplicação do Cubo, a Trissecção do Ângulo, a Quadratura do Círculo e a construção de Polígonos Regulares, que ficaram sem solução por mais de dois mil anos. Importantes para os nossos propósitos são as noções de números algébricos, transcendentes e os critérios que decidem sobre a construtibilidade, ou não, desses números. Neste trabalho, reconstituímos algumas etapas das construções geométricas, com régua (sem marcas) e compasso, desde as construções elementares até o desfecho dado, no século XIX, aos problemas acima citados. Destacamos, ainda, a classificação dos polígonos regulares de 3 a 17 lados, quanto a sua construtibilidade.
Euclidean constructions and the ending of the famous problems of geometry
Keywords: números construtíveis; números algébricos; Números Transcendentes; Polígonos regulares; algebraic and transcendental numbers; constructible numbers; regular polygons